2013
DOI: 10.7251/ghte1309029s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Honey Addition on Rheological Properties of Probiotic Soy Yoghurt

Abstract: Yoghurt is a complex rheological system with 3-dimensional network of chains and clusters of casein micelles in which water is entrapped. The gel structure of set-style yoghurt is influenced by many factors that include milk composition, primary dry matter content, protein content and composition, heat treatment of milk. Protein content of milk has the greatest influence on the gel strength, viscosity and syneresis. The aim of this study was to investigate the effect of honey addition at different concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Honey is a functional food with unique ingredients, properties against pathogenic bacteria, and bifidogenic effects. It contains fructooligosaccharides, which act as prebiotics and has various nutrients [14,32]. The preliminary study supported earlier studies that fermented soymilk with 5% honey increased the growth of Lactobacillus casei subsp.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Honey is a functional food with unique ingredients, properties against pathogenic bacteria, and bifidogenic effects. It contains fructooligosaccharides, which act as prebiotics and has various nutrients [14,32]. The preliminary study supported earlier studies that fermented soymilk with 5% honey increased the growth of Lactobacillus casei subsp.…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, honey is a functional food with unique composition that contains fructooligosaccharides acting as prebiotics. Therefore, the addition of honey to fermented milk can increase the growth of bifidobacteria and extend the shelflife of the product via the enhanced lactic acid production and pH lowering [14]. Lactobacillus acidophilus counts were improved in formulas containing honey, soy milk, and aloevera [15].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results, it can be concluded that the use of kombucha and honey is the best combination that contributes to the stability of the drink's structure and indicates a better product quality. Stijepic et al [11] in their research showed a positive effect of adding honey to yogurt on viscosity and water retention capacity, i.e. on reducing the intensity of syneresis.…”
Section: Resultsmentioning
confidence: 98%
“…Syneresis intensity was determined according to the modified method of Koegh and O'Keneedy [10] using a Tehtnica Železniki PLC 322 centrifuge. Samples of the fermented milk drink were centrifuged at 3000 rpm [11], and the volume of separated whey was expressed as ml of centrifuged/100 g of a sample [12].…”
Section: Determining Syneresis Intensitymentioning
confidence: 99%